Linguagem fílmica: uma metáfora de comunicação para a análise dos discursos nas organizações - Freitas, Alessandra Demite Gonçalves de (2012)
This research aims to investigate the filmic language as a metaphor for communication discourse analysis in organizations. To assist in achieving this objective, we studied and compared the content of the speeches made by King George VI in the commercial/ artistic film; the documentary film; the literary work biography; verified with this comparison, the utility also to compare the organizational discourse produced between managers and employees; discussed the phenomenon of communication and contribution of their role for managers and organizations as well as the possible contribution of the use of film language in organizations as a metaphor for communication, for analysis of discourses produced. Was used the qualitative research approach, the phenomenological method and strategy case study. As this is a research of descriptive and exploratory nature, the strategy for data collection was based on research bibliographical and documental, taking as a strategy of collects the indirect observation and non-participant, based on the theoretical and empirical study. The data were collected through observations registered in protocols and, for processing of those data was used the strategy of discourse analysis the personage of King George VI in the film 'The King's Speech'; the strategy documental analysis of the documentary film ' The King Speak "- The true story behind the film '; the strategy of content analysis of the literary work biography 'The King's Speech - as a man saved the British monarchy'. It was observed that the filmic language have been discussed by diverse authors that gradually contributing to the use of case studies with a full commercial/ artistic films in the context of teaching and learning in Administration. The results found have reinforced the use of filmic language in the context of Administration and deepening research that involve this thematic. It was observed in the studied case, from the analysis of the discourses produced in commercial/ artistic film, the relationship between King George VI and his country, as a metaphor of contemporary organizational scenario, in which managers and employees face daily challenges related to communication. Thus, this discussion has contributed to the increased use of filmic language and the use of metaphors. It is hoped that these results can assist the application of new strategies for the management of communication in organizations.